Pengaruh Komite Audit, Ukuran Perusahaan, Dan Tekanan Eksternal Terhadap Kecurangan Laporan Keuangan - Rizki Islami; Syamsuri Syamsuri (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of Audit Committees, Firm Size, And External Pressure On Financial Statement Fraud in industrials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research uses secondary data in the form of annual financial reports obtained from the official IDX website. The sample was determined using a purposive sampling method, resulting in 10 companies with a total of 50 observations over five years. The variables in this study consist of the audit committee (X1), firm size (X2), and external pressure (X3) as independent variables, and financial statement fraud (Y) as the dependent variable. The analytical method employed is logistic data regression using Eviews 13 software. The results show that, partially, the audit committee has a significant effect on financial statement fraud, while firm size and external pressure have no significant effect. However, simultaneously, all three independent variables significantly influence financial statement fraud.